Preparation of isoorientin-zein/gum arabic nanoparticles and their effects on wound healing in mice - MENG Dan; ZHANG Meng; JIA Yingyu; MENG Yan; LUO Ying; YUAN Li (浙江大学学报. 农业与生命科学版)
The effects of isoorientin (Iso)-zein (Zein)/gum arabic (GA) nanoparticles on wound healing were explored in this study. The nanoparticles were prepared via the anti-solvent method. A back skin wound model of mice was constructed and the mice were randomly separated into the control group and Zein/GA, 0.5 mg/mL Iso, 1.0 mg/mL Iso, 0.5 mg/mL Iso-Zein/GA and 1.0 mg/mL Iso-Zein/GA treatment groups. Except the control group, the wound tissues of mice in other treatment groups were treated with solutions of Zein/GA nanoparticles, Iso and Iso-Zein/GA nanoparticles, respectively. Then, the wound healing and body mass changes of mice were observed. The antioxidant indexes of the wound tissues and the relative expression levels of the transforming growth factor-β (TGF-β), interleukin-1β (IL-1β), nitric oxide synthase 2 (NOS2) and tumor necrosis factor-α (TNF-α) were measured, and the histopathological changes, collagen deposition, new blood vessels formation and fibroblast formation of the wound tissues were observed by hematoxylin-eosin staining, Masson staining and immunohistochemical staining tests. The results showed that the wound healing rate of each treatment group was significantly higher than that of the control group on the 10th day of the experiment (P＜0.05), and the wound healing rates of the 1.0 mg/mL Iso, 0.5 mg/mL Iso-Zein/GA and 1.0 mg/mL Iso-Zein/GA treatment groups were significantly higher than that of Zein/GA treatment group (P＜0.05). Compared to the control group, the H2O2 and malondialdehyde levels significantly reduced (P＜0.05), while the activity of glutathione peroxidase significantly increased (P＜0.05) in each treatment group. In the 1.0 mg/mL Iso-Zein/GA treatment group, the inflammatory cell infiltration was visibly reduced, the granulation tissue was abundant, the new blood vessels and fibroblasts were significantly increased, and collagen deposition was obvious. The relative expression level of TGF-β was significantly increased (P＜0.05), and the relative expression levels of IL-1β, NOS2 and TNF-α were significantly decreased (P＜0.05). In summary, Iso-loaded Zein/GA nanoparticles can effectively improve the wound healing in mice compared to Iso, and there may be a dose-dependent effect.